The management of dorsal peroneal nerve compression in the midfoot. (June 2018) - Dhinsa, Baljinder Singh; Hussain, Laila; Singh, Sam
Highlights: Midfoot pain may result from DPN compression. Bony or soft tissue impingement may be present. Diagnosis is based on history and careful clinical examination. Local anaesthetic infiltration maybe diagnostic. Good clinical outcomes from decompression. Abstract: The foot and ankle specialist will frequently encounter patients with dorsal midfoot pain in clinic. In the presence of midfoot pain and/or paraesthesia, nerve entrapment must be considered. The authors report the outcome of a case series of patients who underwent surgical release of the DPN. Between 2011–2017, a single surgeon operated on seven patients with a diagnosis of DPN entrapment. A retrospective review of the patient's clinical notes was performed, including the operative findings. The average age at presentation was 47 years (range, 31–70 years), and the left foot was affected in four cases. In all cases the patient presented with dorsal midfoot pain, with three cases associated with paraesthesia. The mean follow up was 25 months (range, 4–70 months), with six of the patients discharged with their pre-operative symptoms settled. One patient who had good immediate pain relief following DPN neurolysis, EHB tendon resection and reduction of exostosis developed recurrence of the neuropathic pain at five years. Despite non-operative management the symptoms did not settle and exploration of the DPN was performed. The anatomical position of the DPN, and its site of compression, may vary however it can be localised by a positive Tinel's sign and targeted injection with local anaesthetic. All the patients that underwent surgical exploration and decompression had a good outcome, with one patient requiring further neurolysis for impingement.